Kvalitativna analiza intervjuja v etnoloških raziskavah - Huzjan Gabrijelčič, Vanja (Traditiones (Ljubljana), 2000)
Based on several examples, the paper looks at qualitative text analysis. Aside from trying to illustrate certain concepts, hypoteses, even theory, from the viewpoint of the narrator, qualitative analysis at the same time offers the perspective from the researcher's position as well
Keywords: ethnology; etnologija; etnološke raziskave